Skrining Fitokimia Dan Efek Antikoagulan Eliksir Dari Ekstrak Buah Mengkudu (Morinda citrifolia L.) Pada Tikus Putih - Santoso, Puguh; Putri, Noviana; Wibawa, Agung Ari Chandra (Usadha, 2025)
The increasing prevalence of thrombosis as a manifestation of hemostatic dysfunction has prompted the search for safer and more accessible alternative anticoagulant agents. Morinda citrifolia L. (noni fruit) contains various bioactive compounds suspected to modulate blood coagulation pathways. This study aimed to evaluate the anticoagulant effectiveness of an elixir formulated from ethanolic extract of noni fruit on the bleeding time of male white rats (Rattus norvegicus). A post-test only randomized group design was employed, consisting of four treatment groups: negative control (aquadest), positive control (acetosal 80 mg), elixir at 40 mg/kgBW, and elixir at 80 mg/kgBW. The extract was prepared by ethanol maceration and then formulated into elixirs, followed by physical quality testing. Anticoagulant activity was assessed by measuring tail bleeding time. Results indicated that the elixir at 80 mg/kgBW significantly prolonged the bleeding time compared to other groups. Phytochemical screening revealed the presence of flavonoids, tannins, alkaloids, and steroids as dominant constituents. The findings demonstrate that the noni fruit elixir possesses anticoagulant activity, with the higher dose yielding the most pronounced effect. This study concludes that Morinda citrifolia has strong potential to be developed as a natural anticoagulant in pharmaceutical applications.